Fisioterapia no tratamento da dor orofacial de pacientes com disfunção temporomandibular crônica - Franco, Ana Lúcia [UNESP]; Zamperini, Camila Andrade [UNESP]; Salata, Danieli Cristina; Silva, Elaine Cristina; Júnior, Wanderley Albino; Camparis, Cinara Maria [UNESP] (My University, 2011)
Recent studies have shown consistent results using the physical therapy in cases of pain and limitation of movement from temporomandibular dysfunction. Thus, our objective was to assess the effect of ten sessions of physical therapy and laser therapy in treatment of muscular pain and arthralgias in a woman with temporomandibular dysfunction. The painful symptoms relief achieved by session was over 20 %, up to zero at the end of treatment. Results demonstrated that the treatment protocol used was effective to reduce the temporomandibular joint and the masseter muscle tension and a decreased of drugs by patient. However, more studies are needed to define with more accuracy the effect of other physiotherapy programs and its interaction with other treatment modalities.
Physiotherapy as treatment of orofacial pain in patients with chronic temporomandibular dysfunction
Keywords: Facial pain; Laser therapy; Muscular strengthening exercises; Physical therapy; Temporomandibular joint